2019
DOI: 10.3389/fphys.2019.00171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Intervention With Maternal Fecal Bacteria and Antibiotics on Liver Metabolome and Transcription in Neonatal Pigs

Abstract: The establishment of a stable bacterial flora in early life is associated with host metabolism. Studies of fecal microbiota transplantation (FMT) and antibiotics on neonatal pig mainly focused on intestinal development and mucosal immunity, but the information on metabolism is lacking. The objective of this study was to investigate the responses of metabolome and transcriptome in the livers of neonatal piglets that were orally inoculated with maternal fecal bacteria suspension and amoxicillin (AM) solution. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The symbiosis of these core microbiome plays an important role in regulating nutrient metabolism and immunity of the host, ultimately contributing to the health and production performance of pigs ( Geng et al., 2018 ; Kang et al., 2017 ). To date, a myriad of studies have reported that gut microbiota has a high correlation with the immunity, intestinal development, and production performance of swine ( Arnal et al., 2014 ; McCormack et al., 2017 ; Saavedra and Dattilo, 2012 ; Wan et al., 2019 ; Yang et al., 2018a , 2018b ). Specifically, Mach et al.…”
Section: Swine Gut Microbiota and Their Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symbiosis of these core microbiome plays an important role in regulating nutrient metabolism and immunity of the host, ultimately contributing to the health and production performance of pigs ( Geng et al., 2018 ; Kang et al., 2017 ). To date, a myriad of studies have reported that gut microbiota has a high correlation with the immunity, intestinal development, and production performance of swine ( Arnal et al., 2014 ; McCormack et al., 2017 ; Saavedra and Dattilo, 2012 ; Wan et al., 2019 ; Yang et al., 2018a , 2018b ). Specifically, Mach et al.…”
Section: Swine Gut Microbiota and Their Influencing Factorsmentioning
confidence: 99%
“…In addition, other intervention approaches (e.g. faecal microbial transplantation and early feeding) affect the composition and function of gut microbiota ( Cheng et al., 2018 ; Lin et al., 2018 ; Shi et al., 2018 ; Wan et al., 2019 ; Xu et al., 2020 ).…”
Section: Swine Gut Microbiota and Their Influencing Factorsmentioning
confidence: 99%
“…Altered patterns of community assembly in young hosts has been associated with dysbiosis ( Neuman et al, 2018 ) and increased susceptibility to disease ( Arruda et al, 2013 ). Conversely, microbiome management strategies are often most successful when applied in the earlier stages of community assembly in host microbiomes ( Lin et al, 2018 ; Wan et al, 2019 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The down-regulation of 1-Pyrroline-5-carboxylate dehydrogenase might be related to the inhibition of the TCA cycle and the oxidative decarboxylation of isocitrate, which would reduce the production of energy and the supplementation of NADP. Additionally, arginosuccinate synthetase catalyzes the transformation of aspartate into arginine, which serves as the penultimate step of arginine biosynthesis [41], all of this information suggests that protein synthesis was inhibited during treatment with actinomycin D.…”
Section: Discussionmentioning
confidence: 99%